Characteristics and source apportionment of black carbon in the Helsinki metropolitan area, Finland. (October 2018) - Helin, Aku; Niemi, Jarkko V.; Virkkula, Aki; Pirjola, Liisa; Teinilä, Kimmo; Backman, John; Aurela, Minna; Saarikoski, Sanna; Rönkkö, Topi; Asmi, Eija; Timonen, Hilkka
Abstract: Black carbon is emitted from the incomplete combustion of carbonaceous fuels and will detrimentally affect air quality, climate and human health. In this study, equivalent black carbon (eBC) concentrations were measured by using an aethalometer (AE33) at three different locations in the Helsinki metropolitan area, Finland from October 2015 to May 2017. One sampling site was located in an urban street canyon (SC, sampling period 18 months) and two of the sampling sites were located in suburban detached house (DH) areas (DH1, 13 months and DH2, 5 months). Based on the campaign averages, the eBC concentration levels were higher at the street canyon site (1690 ± 1520 ng/m 3 ) than at the residential detached house areas (DH1 = 880 ± 1500 ng/m 3 and DH2 = 1040 ± 2130 ng/m 3 ). The contribution of eBC from fossil fuel (BCFF ) and wood burning (BCWB ) were estimated based on the spectral dependence of light absorption of different sources. The spectral behavior is described using absorption Ångström exponent (α) values for both fossil fuel (αFF ) and wood burning (αWB ) that were determined using concurrent wood burning tracer (levoglucosan) measurements. Based on the source apportionment, the contribution of BCWB to eBC was clearly higher at the detached house area sites DH1 (41 ± 14%) and DH2 (46 ± 15%) than at the urban street canyon site (15 ± 14%). A distinct seasonal dependency was observed in the eBC concentration levels at the detached house areas. The highest concentrations were detected during the cold seasons due to residential wood combustion. On the opposite, at the SC site, the concentration levels of eBC were rather constant throughout the campaign, being dominated by the BCFF emissions from close-by vehicular traffic. Substantial temporal and spatial variability in eBC concentrations and sources were observed within the Helsinki metropolitan area. eBC is shown to be closely tied to the characteristics of the measurement site, season, meteorological conditions and the time of the day. Highlights: Long-term black carbon (BC) measurements performed at three different locations. Source apportionment of BC from fossil fuel and wood burning sources. Substantial temporal and spatial variability in BC sources were observed. At the detached house areas the highest BC levels were observed during winter. At the street canyon site BC concentrations and sources were relatively constant.